Epidemiology of Hypertension and Diabetes Mellitus in Latin America - Lopez-Jaramillo, Patricio; Lopez-Lopez, Jose; Cohen, Daniel; Alarcon-Ariza, Natalia; Mogollon-Zehr, Margarita (Current Hypertension Reviews, 2021)
Hypertension and type 2 diabetes mellitus are two important risk factors that contribute to cardiovascular diseases worldwide. In Latin America, hypertension prevalence varies from 30 to 50%. Moreover, the proportion of awareness, treatment and control of hypertension is very low. The prevalence of type 2 diabetes mellitus varies from 8 to 13% and around 40% of patients are unaware of their condition. In addition, the prevalence of prediabetes varies from 6 to 14% and this condition has also been associated with increased risk of cardiovascular diseases. The principal factors linked to a higher risk of hypertension in Latin America are increased adiposity, low muscle strength, unhealthy diet, low physical activity and low education. Besides being chronic conditions, leading causes of cardiovascular mortality, both hypertension and type 2 diabetes mellitus, represent a substantial cost for the weak health systems of Latin American countries. Therefore, it is necessary to implement and reinforce public health programs to improve awareness, treatment and control of hypertension and type 2 diabetes mellitus, in order to reach the mandate of the United Nations to decrease the premature mortality for CVD.
Keywords: cardiovascular disease